IDNLearn.com connects you with a community of experts ready to answer your questions. Join our Q&A platform to receive prompt and accurate responses from knowledgeable professionals in various fields.
Sagot :
To solve for [tex]\((f - g)(2)\)[/tex], we need to understand that this expression represents the difference between the functions [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] evaluated at [tex]\(x = 2\)[/tex].
1. Evaluate [tex]\(f(x)\)[/tex] at [tex]\(x = 2\)[/tex]:
Recall the function [tex]\(f(x) = 3x^2 + 1\)[/tex].
Plug in [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 1 \][/tex]
Calculate the square of 2:
[tex]\[ (2)^2 = 4 \][/tex]
Multiply by 3:
[tex]\[ 3 \times 4 = 12 \][/tex]
Add 1:
[tex]\[ 12 + 1 = 13 \][/tex]
Therefore,
[tex]\[ f(2) = 13 \][/tex]
2. Evaluate [tex]\(g(x)\)[/tex] at [tex]\(x = 2\)[/tex]:
Recall the function [tex]\(g(x) = 1 - x\)[/tex].
Plug in [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 1 - 2 \][/tex]
Subtract 2 from 1:
[tex]\[ 1 - 2 = -1 \][/tex]
Therefore,
[tex]\[ g(2) = -1 \][/tex]
3. Combine the results to find [tex]\((f - g)(2)\)[/tex]:
The expression [tex]\((f - g)(2)\)[/tex] is found by subtracting [tex]\(g(2)\)[/tex] from [tex]\(f(2)\)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2) \][/tex]
Substitute the values we calculated:
[tex]\[ (f - g)(2) = 13 - (-1) \][/tex]
This simplifies to:
[tex]\[ 13 + 1 = 14 \][/tex]
So, the value of [tex]\((f - g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
1. Evaluate [tex]\(f(x)\)[/tex] at [tex]\(x = 2\)[/tex]:
Recall the function [tex]\(f(x) = 3x^2 + 1\)[/tex].
Plug in [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 1 \][/tex]
Calculate the square of 2:
[tex]\[ (2)^2 = 4 \][/tex]
Multiply by 3:
[tex]\[ 3 \times 4 = 12 \][/tex]
Add 1:
[tex]\[ 12 + 1 = 13 \][/tex]
Therefore,
[tex]\[ f(2) = 13 \][/tex]
2. Evaluate [tex]\(g(x)\)[/tex] at [tex]\(x = 2\)[/tex]:
Recall the function [tex]\(g(x) = 1 - x\)[/tex].
Plug in [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 1 - 2 \][/tex]
Subtract 2 from 1:
[tex]\[ 1 - 2 = -1 \][/tex]
Therefore,
[tex]\[ g(2) = -1 \][/tex]
3. Combine the results to find [tex]\((f - g)(2)\)[/tex]:
The expression [tex]\((f - g)(2)\)[/tex] is found by subtracting [tex]\(g(2)\)[/tex] from [tex]\(f(2)\)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2) \][/tex]
Substitute the values we calculated:
[tex]\[ (f - g)(2) = 13 - (-1) \][/tex]
This simplifies to:
[tex]\[ 13 + 1 = 14 \][/tex]
So, the value of [tex]\((f - g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Trust IDNLearn.com for all your queries. We appreciate your visit and hope to assist you again soon.